Decoding the reaction mechanism of the cyclocondensation of ethyl acetate2‐oxo‐2‐(4‐oxo‐4H‐pyrido [1.2‐a] pyrimidin‐3‐yl) polyazaheterocycle and ethylenediamine using bond evolution theory. Issue 14 (5th April 2022) - Maraf, Mbah Bake; Idrice, Adjieufack Abel; Mekoung Pélagie, Manwal A.; Zintchem, Auguste Abouem A.; Bebga, Gouet; Rhyman, Lydia; Ibrahim, Mbouombouo Ndassa; Ramasami, Ponnadurai
Abstract: We investigated the flow of electron density along the cyclocondensation reaction between ethyl acetate 2‐oxo‐2‐(4‐oxo‐4 H ‐pyrido[1.2‐a]pyrimidin‐3‐yl) polyazaheterocycle (1 ) and ethylenediamine (2 ) at the ωB97XD/6–311++G(d, p)computational method within of bond evolution theory (BET). The exploration of potential energy surface shows that this reaction has three channels (1–3) with the formation of product 3 via channel‐2 (the most favorable one) as the main product and this is in good agreement with experimental observations. The BET analysis allows identifying unambiguously the main chemical events happening along channel‐2. The mechanism along first step (TS2‐a) is described by a series of four structural stability domains (SSDs), while five SSDs for the last two steps (TS2‐b and TS2‐c). The first and third steps can be summarized as follows, the formation of N1‐C6 bond (SSD‐II), then, the restoration of the nitrogen N1 lone pair (SSD‐III), and finally, the formation of the last O1‐H1 bond (SSD‐IV). For the second step, the formation of hydroxide ion is noted, as a result of the disappearance of V(C6, O7) basin and the transformation of C6‐N1 single bond into double one (SSD‐IV). Finally, the appearance of V(O7, H2) basin lead to the elimination of water molecule within the last domain is observed. Abstract : Evolution population (in electrons) of selected basins along the IRC associated respectively with TS2‐a, TS2‐b and TS2‐c reactions pathways